Absence of effect of simvastatin on the progression of lens opacities in a randomised placebo controlled study. Oxford Cholesterol Study Group. Issue 11 (November 1995) - Harris, M L; Bron, A J; Brown, N A; Keech, A C; Wallendszus, K R; Armitage, J M; MacMahon, S; Snibson, G; Collins, R
Abstract : AIMS--A detailed assessment of ophthalmic effects of an HMG CoA reductase inhibitor, simvastatin, was performed. METHODS--Six hundred and twenty one individuals considered to be at increased risk of coronary heart disease were randomised, following an 8 week placebo 'run in' period, to receive 40 mg daily simvastatin, 20 mg daily simvastatin, or matching placebo. Patients with a baseline corrected visual acuity better than 6/24 and without a history of cataract were eligible for detailed ophthalmic assessment at 6 months (539 patients assessed) and at 18 months (474 patients assessed). RESULTS--No significant differences between the treatment groups were detected at the 6 month or 18 month visit in the refractive condition of the eye or in the mean intraocular pressure. Nor were there clear differences in the Oxford grading system scores for various measures of the major types of cataract (cortical spokes, posterior subcapsular cataract, nuclear brunescence, white scatter) or for other morphological features visible within the lens (fibre folds or focal dots). Scheimpflug slit image photographs and retroillumination analysis of the percentage of cataract within a defined region of the lens were also performed at each visit, with no clear differences observed between the treatment groups. CONCLUSION--This single centre double blind study found no good evidence of any adverse effects of 18 months of simvastatin treatment on lens opacity formation, using a variety of validated techniques to assess cataract development. Routine clinic follow up of visual symptoms and admission to hospital for ophthalmic procedures over 5 years of treatment was also reassuring, with no excess adverse outcomes observed with simvastatin.